Optimized Surface Adjustment Method for Large Deployable Cable Network Antennas - Xin Zhang; Lipeng Wang; Xiaofei Ma; Yizhe Wang (International Journal of Antennas and Propagation)
Large deployable mesh reflectors typically require high surface accuracy and have large apertures. The accumulation of machining errors in a large number of cables can lead to significant deviations between the final manufactured surface and the theoretical surface, particularly due to the large number of cables involved. Adjusting the mesh reflector is often necessary to meet the surface accuracy requirements. However, traditional surface adjustment methods can be challenging to converge and time-consuming. To address this issue, our paper proposes an engineering surface based on measured manufacturing errors as a substitute for the theoretical surface. This method can save time on the coarse adjustment of surface accuracy for large deployable mesh reflectors, reducing the overall surface accuracy adjustment time by 30%.